Em nome da audiência : estudo de recepção com telespectadores das telenovelas bíblicas exibidas pela Record TV - Santos, Alliston Fellipe Nascimento dos (2021)
A pioneer in the field of religious teledramaturgy in Brazil, Record TV invests, as of 2015, in biblical soap operas, derived from the scriptures of the Holy Bible. Os Dez Mandamentos (The Ten Commandments) and A Terra Prometida (The Promised Land), aired by the broadcaster in 2015 and 2016 respectively, gained space with audiences and became the broadcaster's main product. Since then, other plots of the same nature have been produced and shown. In this sense, the project presented a qualitative and exploratory study of the reasons that would lead the audience to be interested in biblical telenovelas, primarily in an environment where the soap operas from the broadcaster Rede Globo de Televisão have always been predominant. Therefore, we proposed a study with the aim of understanding the motivations that lead two specific groups of receivers to follow these fictional television products: 1- people who consider themselves institutionalized Christians (who attend church); 2- people who believe in Christian dogmas, but do not attend church, identifying consonances and dissonances about these motivations and proposing a discussion regarding overlapping sociocultural aspects. The methodological assumptions for the execution of the research were based on the theoretical approach of Uses and Gratifications, from the perspective of Grounded Theory. To obtain the data, in-depth interviews were conducted with viewers who declared themselves consumers of biblical soap operas, and who are part of an intentional stratified sample to ensure internal diversity to it and potentially generate plurality of responses, aiming to achieve the objectives proposed by this study. According to the results, we categorized five main motivations: while the institutionalized audience is motivated to follow the biblical narratives by 1- Christian content, 2- Social/familiar integration, the noninstitutionalized audience is motivated by 3- Learning/counseling, 4- stress relief/relaxation. Finally, the only motivation present in both groups was categorized as 5- Journey to the past.